Drivers of Women Entrepreneurship in the Autonomous Region in Muslim Mindanao - Emraida C. Ali DBA; Noraida C. Ali DBM (Procedia of Social Sciences and Humanities, 2021)
This is a quantitative study conducted to analyze the drivers of women entrepreneurship in the Autonomous Region in Muslim Mindanao. The descriptive- correlation research design was used to execute the research and analyze the data. The respondents were the selected women entrepreneurs in the provinces of Maguindanao, Lanao del Sur, Basilan, Sulu and Tawi-tawi. A modified research questionnaire was used in this study as the main data-gathering instrument. Data were analyzed using the frequency, percentage, mean, and multiple regression analysis. The personal entrepreneurial competency, presence of entrepreneurial role model, government programs and interventions, motivation are studied whether it influence the extent of women entrepreneurship in terms of involvement in the four phases of entrepreneurial activity: searching; planning; marshaling; and implementing. Results of the study revealed that significant predictors are the personal entrepreneurial competency, government programs and interventions, and motivation. Among these significant predictors, the personal entrepreneurial competency has the highest contribution thus making it the best predictor of women entrepreneurship